Are people willing to tell pareto white lies? A review and new experimental evidence - Edward Cartwright; Lian Xue; Charlotte Brown (Games, 2021)
We explore whether individuals are averse to telling a Pareto white lie-a lie that benefits both themselves and another. We first review and summarize the existing evidence on Pareto white lies. We find that the evidence is relatively limited and varied in its conclusions. We then present new experimental results obtained using a coin-tossing experiment. Results are provided for both the UK and China. We find evidence of willingness to tell a partial lie (i.e., inflating reports slightly) and high levels of aversion to telling a Pareto white lie that would maximize payoffs. We also find no significant difference between willingness to tell a Pareto white lie and a selfish black lie-a lie that harms another. We find marginal evidence of more lying in China than the UK, but the overall results in the UK and China are very similar.
Keywords: 330; altruistic lie; dishonesty; lie aversion; Pareto white lie; selfish lie